Where Do You Sit in Class? A Study of Spatial Positioning During Two Courses of Different Duration - Gilles Clément; Angie Bukley (Journal of Human Psychology, 2017)
The objective of this study was to study the selection of seat location by individuals in a group in a confined environment and to identify the factors leading people to prefer one location to another. We analyzed the seating location of students in a lecture hall over the course of two academic programs of different durations (19 days and 44 days). The goal was to determine the rate at which participants would settle into a specific seat location. Unobtrusive photography was used to collect objective data on an hourly basis. Results showed that in both courses participants began to settle into a specific location from the second day of class. Twenty percent of the participants had settled after 4-7 days or 15.5 hours in class. Settling continued for the duration of the shorter course. However, in the longer course settling stopped after 28.5 days on average. The plateau in the number of settlers depended on the number of days, not on the time actually spent in class. At the end of the longer course 52.5% of the participants had settled, compared to 38.9% in the shorter course. Settling into the same seat location can be interpreted as a strategy to establish a personal territory. These results indicate that about half of a cohort expresses the need for establishing a personal territory when in a confined and crowded environment, and this process takes about one month.
Keywords: Spatial exploration